Selected African American First-Time Teenage Mothers' Perceptions of Nurse Caring Behaviors During The Postpartum Period - Potter, Danita Renae; Condon, Esther H.; Montgomery, Arlene J.; Muhammad, Toni Sims; McGee, Zina T. (International Journal of Advanced Nursing Studies, 2012)
The purpose of this study was to explore and describe African American teen mothers’ perceptions of nurse caring behaviors during the postpartum period in a rural southern state. African Americans have unique cultural needs; thus, it is critical for the science of nursing to explore and describe African American teenage mothers’ perceptions of nurse caring behaviors during the postpartum period. By exploring and describing African American first-time teenage mothers’ perceptions of nurse caring behaviors, the researcher will help nursing science gain insight into how to facilitate and enhance postpartum care for young families. An exploratory descriptive design was used and descriptive analyses were conducted on demographic characteristics and CBA subscales to answer the research question:  How do African American first-time teenage mothers describe nursing behaviors and identify the most important nursing behaviors that they received during the postpartum period?  Findings indicated that there was statistical significance for the independent variable, decision making for your health, and the Caring Behaviors Assessment (CBA) subscales of humanism/faith-hope/sensitivity (p = 0.050), human needs assistance (p = 0.052), and the demographic characteristics. The analysis revealed attentive to needs was a common theme.